PENGARUH INOVASI PRODUK, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN SEPEDA MOTOR HONDA (SURVEI PADA PELANGGAN PT. TUNAS DWIPA MATRA NATAR) - Dwi Safitri; Dian Komarsyah Djuardi; Fenny Saptiani (Jurnal Kompetitif Bisnis, 2022)
The purpose of this study was to ascertain the extent to which product innovation, price, and service quality affect customer satisfaction towards Honda motorcycles. This study was descriptive in nature and employed a quantitative approach. Customers of PT. Tunas Dwipa Matra Natar in South Lampung comprised the population of this study. This study employed a purposive sampling technique with a research sample of 100 customers. In November 2021, data collection was conducted using questionnaires and observations. Multiple linear regression analysis was used to analyze the data in this study, which was conducted using the SPPSS 25 application. According to the research and data analysis findings, product innovation has a significant impact on customer satisfaction, price has a significant impact on customer satisfaction, and service quality has a significant impact on customer satisfaction. Additionally, at PT. Tunas Dwipa Matra Natar, product innovation, price, and service quality all have a positive and significant impact on customer satisfaction.